Soccer greats : the best of all time - Streissguth, Thomas, 1958- (ReferencePoint Press, Inc., 2026)
"Since organized soccer began in nineteenth century England, the sport has become the most popular in the world. Skill, strength, and game smarts are all part of top-league soccer talent. Soccer pros have to handle the grind of constant training, long-distance travel, and high pressure matches. Just a handful can be considered among the GOATs: the greatest of all time. The argument over the all-time greats has been going on since organized football began"--